MENGURANGI KEKERASAN TERHADAP ANAK BERBASIS PENDEKATAN PENDIDIKAN MULTIKULTURAL - Nur Kholis (AL-TAHRIR, 2014)
Abstract: Humans  have  their  own  potential  as  an  instrument  to perfect their existence. In the process of perfecting, they always do some  processes  as  well  as  social  interactions  to  optimize  any potential  they  had  by  synchronizing  internal  and  external  poten-tials of  their  social  environment. A phenomenon  shows  that  there are  two  possibilities  resulted  by  the  process:  harmony  or  clash. The  process  of  harmony  is  indicated  by  accomplishment  of  any objectives  or  needs  of  each  individual  that  does  the  social interaction. On  the  contrary,  the  clash process will happen  if  the interactions  turn  to  violence  on  weak/poor  individual  or  group, either structurally or culturally, socially, and economically. One of causes  of  the  clash  resulting  violence  is  the  absence  of  social control,  imbalance  of  hierarchical  interaction,  social  imbalance and  poor  economy.  Multicultural  education  can  be  set  as  an approach  in  learning/education  in  Indonesia  by  firstly  examining its philosophical background and  educational  theory which,  then, leads  to  the  method(s)  and  technique(s)  of  learning/education  to shape generation that have the following characteristics: tolerated, social-characterized,  and  aware  to  certainty  of  diversity  as sunatullah  that  hopefully  results  in  decreasing  clash  phenomena which lead to any violence or conflict.